KONDISI OSEANOGRAFI DI SELAT MATAK KABUPATEN KEPULAUAN ANAMBAS MELALUI MODEL HIDRODINAMIKA - Riyadi, Agung; said, nusa idaman; Santos, Matih (Center for Environmental Technology, 2014)
This paper describes some of the general condition of the oceanographic parameters in the Strait Matak, Anambas Archipelago. The data flow is obtained by direct measurement by using a current meter types RCM-7. Simulation models using Mike 21. Mike flow pattern is divided into two seasons, namely west season (January) and the east season (August) and flow patterns ahead of the tide when the season is generally moving west to wards the south, it demonstrates the role of strong tidal influence the movement of waterin the study area. Flow velocity in the strait just before the tide on the west season reaches 1m/s.Ã‚Â Flow patterns at high tide on the west season looks still moving toward sthe south. The maximum flow velocity in the strait when the tide reaches 0.32 m/s, while the average speed in the area of the model is 0.12 m/s. Low tide towards the current pattern is still moving towards the south, it reinforces the notion that in addition to tidal windsare also very significant role in moving the flow, in this case that the current is moving toward the south. Flow velocity just before low tide reaches 0.85 m/s. Flow patterns at low tide shows the differences in the three previous conditions, the current in the strait to move out to the north toward the South China Sea. In condition slow tide, the tida lmore dominantly than the wind, this proved to even though the wind toward the south, the currents inthestraitis moving toward snorth along the tidal flow leading to the South China Sea. Flow velocity is quite varied location of modeling; flow velocity at low tide reaches 0.5m/s, with the average 0.15 m/s.Ã‚Â Keywords: current and direction, wind, tide, model.